PENGUKURAN NILAI TARGET STRENGTH DAN ACOUSTIC FISH DENSITY DI PERAIRAN PULAU TIDUNG, KEPULAUAN SERIBU - Farhan, Muhammad; Manik, Henry Munandar; Hestirianoto, Totok (Jurnal Teknologi Perikanan dan Kelautan, 2023)
Information on fish density is still not accurate, because the data obtained are not directly measured in real conditions of the waters. To overcome this problem, we used hydroacoustic technology of echosounder i.e., a Single Beam Echosounder (SBES) SIMRAD EK 15 with a frequency of 200 kHz. This study aimed to examine and interpret the measurement results of target strength and acoustic fish density in the waters of Tidung Island, Kepulauan Seribu in order to obtain a visualization of fish density and determine the relationship between target strength, fish density, temperature and salinity. Data processing used Sonar 5-Pro, Matlab 2016, and Minitab 16. TS in Tidung Island waters were -59,4 dB to -34,6 dB. The highest fish density value was found at station 3 at a depth of 12-21 m at 778,1 ind/m3 the lowest fish density was at station 6 at a depth of 2-11 m at 0,3 ind/m3. Temperature and salinity had various values with values ranging from 29,6°C to 31,2°C and 32,2 PSU to 33,3 PSU. The results of PCA analysis of TS and fish density had a stronger relationship with temperature than salinity.